EDUKASI KANDUNGAN BAHAYA BAHAN KIMIA TRICLOSAN PADA HANDSANITIZER - Harningsih, Tri (Jurnal Media Tropika, 2022)
Hand sanitizer is a health product that can instantly kill germs without using water. One of the preventive measures to prevent the transmission of the Corona virus is to always wash your hands with soap and hand sanitizer as a substitute for soap. The alcohol content in hand sanitizers is considered less safe because alcohol is an organic solvent that can dissolve sebum on the skin. The purpose of this service activity is to find out the dangers of using triclosan in hand sanitizers with the target community in Baki Village, Pandeyan, Sukoharjo. The method of implementing community service is in the form of direct counseling with pre-test and post-test about the content and dangers of the chemical triclosan in hand sanitizers. This service activity was successful with a target of 100% attendance. The results of the participants pre-test and post-test experienced a significant change. The satisfaction questionnaire that has been filled in by the PKK mothers has the highest average value of 4.3 and is categorized on a good scale value. The service activities ran smoothly and provided many benefits for PKK women in Baki Village, Pandeyan, Sukoharjo. Keywords: corona, hand sanitizer, triclosan